IRUTION AND DENSITY OF POPULATION 1954.66. - Hartley , Robert G. (مجلة كلية الاداب, 1969)
Elaboration of the distributional and density patterns of Lihva's population indicates some of the causes, characteristics and consequences of the country's demographic change. As Zelinsky maintained... « If we learn to explain numbers, more than half the battle has been won in explaining the location of age groups, lite racy and mortality, etc. » Spengler? has been more specific in iden tifying the economic-demographic interrelations of population dis tribution. Defined as secondary demographic variables, distribu tion, and hence density, are determined by dynamic variables of fertility, mortality and migration. In turn, numerical aspects of the population influence, and respond to, changes in net national product, distribution of income, employment, investment, consump tion and savings. In short, the distributional aspects of population are sensitive indicators of economic and demographic change.